Analisis Kualitas Pelayanan Publik di Kantor Kecamatan Maniangpajo Kabupaten Wajo - Andi Abrar Asbi; Mastura Karateng; Ekayani Burhanuddin (Kajian Administrasi Publik dan ilmu Komunikasi, 2025)
Quality public service is what is called the best service that meets service quality standards. Service standards are the benchmarks used as guidelines for the delivery of service and the reference for evaluating the quality of service as the obligation and promise of the service providers to the community in the context of quality, fast, affordable, and measurable service. The purpose of this study is to assess the quality of public service at the Maniangpajo Subdistrict office and to identify the factors affecting the quality of public service at the Maniangpajo Subdistrict office. This research uses a qualitative method with a population of 5 individuals, consisting of civil servants (2 people) and the public (3 people). Data collection was done using observation, interviews, and documentation techniques, while the data analysis technique used in this study is qualitative analysis, specifically the interactive analysis technique.The results of this study show that the service at the Maniangpajo Subdistrict office is considered good by service users because the staff are proactive in providing information and the waiting room is comfortable. Although there are no specific SOPs in place, they apply service standards in accordance with government regulations. However, issues such as limited human resources and the unavailability of ID card forms cause delays in service.For internal factors, it can be concluded that the main obstacle to service delivery at the Maniangpajo Subdistrict office is frequent internet network disruptions. These disruptions slow down the service process that requires internet connectivity. Additionally, internal factors such as the limited number of service personnel also affect the efficiency of service, especially when many service users are present, resulting in long waiting times.